El Mesolítico en Cantabria centro-oriental - Perez Bartolomé, Mercedes, (Access archaeology., 2019)
This text explores the Mesolithic period in the central-eastern area of Cantabria (Spain) as a manifestation of sociocultural evolution and change of the societies that lived in the area between the ninth and sixth millennia cal BC, until the introduction of farming.